De Novo Transcriptome of Mammillaria bombycina (Cactaceae) under In Vitro Conditions and Identification of Glyoxalase Genes - Carolina Enríquez-González; Cristina Garcidueñas-Piña; Osvaldo Adrián Castellanos-Hernández; Sergio Enríquez-Aranda; Abraham Loera-Muro; Gilberto Ocampo; Eugenio Pérez-Molphe Balch; José Francisco Morales-Domínguez (Plants, 2022)
Mammillaria bombycina is a cactus distributed in the central region of Mexico. Cactaceae have the particularity of surviving drought and high temperatures, which is why in vitro propagation studies have been carried out successfully to preserve this species and use it as a study model in cacti. In this contribution, a de novo transcriptome of M. bombycina was produced under in vitro conditions for the identification and expression of genes related to abiotic stress. Samples were sequenced using an Illumina platform, averaging 24 million clean readings. From assembly and annotation, 84,975 transcripts were generated, 55% of which were unigenes. Among these, the presence of 13 isoforms of genes belonging to glyoxalase I, II and III were identified. An analysis of the qRT-PCR expression of these genes was performed under in vitro and ex vitro conditions and dehydration at 6 and 24 h. The highest expression was observed under greenhouse conditions and dehydration at 24 h, according to the control. The de novo assembly of the M. bombycina transcriptome remains a study model for future work in cacti.